Glutamine alleviates radiation-induced intestinal injury in rats via the mTOR/Notch1 axis - Lu, Heng; Ni, Xiangmin; Liang, Xinyu; Bai, Qian; Li, Haoyu; Shi, Mengran; Jia, Yulong; Wang, Jian (Frontiers in Oncology, 2026)
IntroductionRadiotherapy remains a principal modality for managing malignant pelvic tumors; nevertheless, it frequently induces radiation-associated intestinal injury (RIII), a debilitating complication that compromises intestinal barrier integrity. Glutamine (Gln) functions as an essential nutrient for maintaining and repairing the intestinal mucosa, yet its specific role in RIII and the mechanisms involved have not been clearly defined.MethodsIn this study, we explored the protective potential and molecular mechanisms of Gln against RIII by employing both a localized abdominal irradiation rat model and irradiated HT-29 cell cultures.ResultsGln administration markedly mitigated intestinal shortening and mucosal injury, reduced the expression of pro-inflammatory cytokines, and restored the number of goblet cells (GCs). Furthermore, Gln treatment enhanced intestinal Lgr5 and Klf4 expression, suggesting protection of intestinal stem cells (ISCs) and facilitation of GC differentiation. Mechanistically, Gln activated the mTOR pathway and its downstream effectors S6K1 and 4E-BP1, while suppressing the radiation-induced overactivation of Notch1. Pharmacologic interventions using rapamycin and Jagged-1 further validated that Gln modulates the mTOR/Notch1 signaling cascade, leading to increased MUC2 expression and improved mucosal integrity.DiscussionCollectively, these results demonstrate that Gln confers robust protection against RIII by regulating the mTOR/Notch1 axis, alleviating Notch1 overactivation, and promoting GC differentiation. These findings provide valuable mechanistic insight and experimental support for Gln as a potential therapeutic agent to prevent or mitigate radiation-induced intestinal injury.